2022
DOI: 10.3390/jcm11133856
|View full text |Cite
|
Sign up to set email alerts
|

Across the Myeloablative Spectrum: Hematopoietic Cell Transplant Conditioning Regimens for Pediatric Patients with Sickle Cell Disease

Abstract: One out of every five hundred African American children in the United States has sickle cell disease (SCD). While multiple disease-modifying therapies are available, hematopoietic cell transplantation (HCT) remains the only curative option for children with SCD. HLA-matched sibling HCT has demonstrated excellent efficacy, but its availability remains limited; alternative donor strategies are increasingly explored. While Busulfan-Cyclophosphamide has become the most widespread conditioning regimen employed in H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 95 publications
(183 reference statements)
0
0
0
Order By: Relevance
“…Busulfan has been studied as a second-line option for treatment in HU resistant and intolerant older adults [29]. Busulfan has been used in those undergoing hematopoietic stem cell transplantation (HSCT) [30,31]. A small case-controlled study involving children indicated that busulfan clearance was not affected by SCD in terms of pharmacokinetics, but that other modifying factors such as organ pathologies and/or co-administered medications may have a different effect in those with SCD [32].…”
Section: Scdmentioning
confidence: 99%
“…Busulfan has been studied as a second-line option for treatment in HU resistant and intolerant older adults [29]. Busulfan has been used in those undergoing hematopoietic stem cell transplantation (HSCT) [30,31]. A small case-controlled study involving children indicated that busulfan clearance was not affected by SCD in terms of pharmacokinetics, but that other modifying factors such as organ pathologies and/or co-administered medications may have a different effect in those with SCD [32].…”
Section: Scdmentioning
confidence: 99%